The Effect of the Numbered Heads Together Cooperative Learning Model on Students' Mathematical Problem-Solving Ability at SMAN 1 Wondama - syamsinar (International Journal of Technology and Education Research, 2026)
This research was motivated by students' low mathematical problem-solving abilities. This quantitative study used a pre-experimental approach and was conducted at SMAN 1 Wondama. The purpose of this study was to determine the effect of the Numbered Heads Together cooperative learning model on the mathematical problem-solving abilities of tenth-grade students at SMAN 1 Wondama.The subjects were 30 tenth-grade students. Data collection techniques used included observation, tests (pretest and posttest), and documentation. Based on the results, the average pretest score was 67.30, while the average posttest score after implementing the Numbered Heads Together cooperative learning model increased to 82.50, with a maximum score of 95 and a minimum score of 60. The results of the hypothesis test using the t-test showed a significance value of 0.000 <0.05, thus concluding that the implementation of the Numbered Heads Together cooperative learning model has a significant effect on the mathematical problem-solving abilities of tenth-grade students at SMAN 1 Wondama.Thus, the Numbered Heads Together cooperative learning model is effective in improving students' mathematical problem-solving skills.